Governance-Performance Relationship: A Re-examination Using Technical Efficiency Measures - Bozec, Yves; Dia, Mohamed; Bozec, Richard (Université d'Ottawa | University of Ottawa, 2008)
The objective of this study is to analyze further the governance-performance relationship while improving on two methodological issues: control for endogeneity and firm performance measurement. To mitigate the endogeneity problem, we, first, focus on sub-samples of firms for which we, ex-ante, expect better corporate governance to cause better performance. Second, we use Generalized Least Square (GLS) regressions for panel data. To control for potential measurement bias, we measure firm performance using Data Envelopment Analysis (DEA). The research is conducted in Canada over a five-year period from 2001 to 2005. Corporate governance is measured based on the ROB corporate governance index published by the Globe and Mail. Overall, the results show that better governed firms are more efficient. This study is in line with a growing number of recent studies that propose alternative measures of firm performance. By using DEA, this study brings together the corporate finance and productivity literature.
Le texte intégral de ce document de travail n''est pas disponible en ligne. Pour plus de renseignements sur ce document, veuillez communiquer avec la Direction de la recherche de l''École de gestion Telfer. The full text of this working paper is not available online. For more information regarding this working paper, please contact the Telfer School of Management Research Office.
Keywords: Canada; panel regression; endogeneity; technical efficiency; DEA; corporate governance indexes; Corporate governance